2012
DOI: 10.1007/s00125-012-2569-2
|View full text |Cite
|
Sign up to set email alerts
|

Increased susceptibility to hypertensive renal disease in streptozotocin-treated diabetic rats is not modulated by salt intake

Abstract: Aims/hypothesis In early type 1 diabetes mellitus, renal salt handling is dysregulated, so that the glomerular filtration rate becomes inversely proportional to salt intake. The salt paradox occurs in both humans and rats and, with low salt intake, results in diabetic hyperfiltration. We tested whether increased salt intake could reduce the susceptibility to injury of non-clipped kidneys in diabetic rats with pre-existing Goldblatt hypertension. Methods Male Long-Evans rats were made hypertensive and half were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 47 publications
3
10
1
Order By: Relevance
“…In other diabetic animal models, an increase of blood pressure after salt loading was reported in Goto Kakizaki (GK) rats, Streptozotocin-induced (STZ) rats, Zucker rats and Wistar fatty rats (Reddy & Kotchen 1992;Suzuki et al 1996;Carlson et al 2000;Hayashida et al 2001;Olearczyk et al 2009;Osorio et al 2009;Zhang et al 2009). On the other hand, blood pressure after salt loading did not change in Long-Evans rats or neonatal STZ rats (Iwase et al 1987;Sima et al 2012). In SDT fatty rats at 12 weeks of age, SBP was increased from 127 mmHg to 191 mmHg by salt intake for 8 weeks (Fig.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In other diabetic animal models, an increase of blood pressure after salt loading was reported in Goto Kakizaki (GK) rats, Streptozotocin-induced (STZ) rats, Zucker rats and Wistar fatty rats (Reddy & Kotchen 1992;Suzuki et al 1996;Carlson et al 2000;Hayashida et al 2001;Olearczyk et al 2009;Osorio et al 2009;Zhang et al 2009). On the other hand, blood pressure after salt loading did not change in Long-Evans rats or neonatal STZ rats (Iwase et al 1987;Sima et al 2012). In SDT fatty rats at 12 weeks of age, SBP was increased from 127 mmHg to 191 mmHg by salt intake for 8 weeks (Fig.…”
Section: Discussionmentioning
confidence: 87%
“…; Sima et al . ). In SDT fatty rats at 12 weeks of age, SBP was increased from 127 mmHg to 191 mmHg by salt intake for 8 weeks (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…The plateau phase of steadystate RBF autoregulation was maintained in one study (993), but the limit of autoregulation was shifted to a lower RPP in many studies (307,612,874,993,1365,1472), independent of PGs (1472). However, other studies reported that RBF autoregulation was impaired within hours of induction of hyperglycemia by STZ and persisted into the established phase of DM with attenuated myogenic (588) and MD-TGF responses (1509).…”
Section: Dmt1mentioning
confidence: 88%
“…Dogs (1047) and some rats (705,707,1365,1566) with 2K,1C hypertension have maintained RBF and GFR autoregulation in the nonclipped kidney, although other studies in rats have reported weak autoregulation (1188,1404,1494) that was improved by NOS inhibition (1494). Blockade of AT 1 receptors in 2K,1C hypertensive rats did not affect RBF autoregulation in the nonclipped kidney but abolished GFR autoregulation (1566), presumably because of a reduced efferent arteriolar resistance.…”
Section: Goldblatt Renovascular Hypertensionmentioning
confidence: 96%
See 1 more Smart Citation